Danau Singkarak sebagai Motor Ekonomi Lokal: Analisis Peran Desa Wisata dalam Peningkatan Pendapatan Masyarakat Lokal - Ruth Sahana Manalu; Cahya Putri Rahmadhani; Mira Susilawarni; Dhio Febriansyah Lubis; M. Taufik Rahmadi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study examines the contribution of tourism village development in the Singkarak Lake area to increasing local community income and welfare. The background of this study is based on the importance of local potential-based development in supporting the village economy and empowering communities in a sustainable manner. Tourism villages are not only nature and culture-based destinations, but also a place for community economic empowerment through active participation in the tourism sector. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and literature studies. The research location is focused on Nagari Sumpur, Tanah Datar Regency, West Sumatra. The results of the study show that the development of tourism villages has had a significant economic impact through the opening of new business opportunities, such as managing homestays, traditional food stalls, local transportation services, and selling regional souvenirs. Community involvement is very high and participatory, reflecting the principle of community-based tourism. In addition to providing additional income for vulnerable groups such as housewives, tourism activities also encourage the growth of supporting sectors such as agriculture, fisheries, and local logistics. However, the study also found various obstacles, especially the lack of formal training, the absence of institutional support, the absence of cooperatives or BUMDes that regulate economic activities collectively, and the unequal distribution of benefits among villagers. This gap shows the need for intervention from the government and external partners in the form of training, empowerment, business assistance, and strengthening inclusive governance. Community optimism towards the long-term prospects of tourism villages is still high, especially with the increasing involvement of the younger generation in digital promotion and management of tourism businesses.